Sistem Pakar Pemilihan Topik Judul Skripsi Dengan Metode Forward Chaining Berbasis Web - Utomo, Ricky Tri; Yo, Ceng Giap (Tech-E, 2017)
Expert Systems are computer-based applications that are used to solve problems as the expert thinks. Many college students majoring in Information Technology are difficult to get the thesis title topic even though it has been reading many journals and looking for some references. Therefore to make it easier college students, then the author wants to create an application where college students majoring in Information Technology can more easily get the thesis title topic so the work of thesis becomes more fluent and not obstructed. This app is web based. In system design, the author used several methods in his research that is method of Analyze, Design, and Implementation. Methods in the design of this expert system even this also used forward chaining method as tracking ahead and best first search method. And also using data collection method mean literature study and questionnaire from system that has been created. The result of Expert System of Thesis Title Topic Selection with Forward Chaining method web based expected to be useful and helpfully college students in getting the thesis title topic. Based on questionnaire that has been shared and filled, it can be said that the Expert System of Thesis Title Topic Selection with Forward Chaining Method Web Based is helpful and beneficial for the college students because it helps college student Information Technology in getting Thesis Title.